Improving Student Knowledge and Understanding of the Greenhouse Gases Effects and Global Climate Change and Their Adaptation and Mitigation Efforts - Latuconsina, Husain (Agrikan Jurnal Agribisnis Perikanan, 2023)
The increase in the greenhouse gas effect has increased the earth's temperature and triggered global climate change, as well as given various negative impacts. Thus, efforts to adaptation and mitigate the impacts of climate change need to be carried out massively through various positive activities, including outreach and education to increase the knowledge and understanding of various parties related to this matter. Socialization and educational activities were carried out on December 5, 2021 with the theme 'Blue Carbon and Mitigation Climate Change Action' which was organized by the Biology Study Program Student Association, Faculty of Mathematics and Natural Sciences, University of Islam Malang, and was attended by 40 participants from students and alumni which took place online using zoom meeting app. Data collection using a questionnaire as a form of evaluation was divided into two stages, including: 1) pre-test questionnaire before presentation of discussion, and 2) Post-test questionnaire after delivery of presentation and discussion. The results of the socialization found that relatively many participants had minimal knowledge and understanding of the greenhouse gases effects, climate change and their impact on life, including mitigation efforts, but the evaluation results showed positive changes in this regard. With increased knowledge and understanding it is hoped that it will influence their behavior to be actively involved in mitigating the impact of global climate change now and in the future. So that activities like this need to be continuously followed up in academic and non-academic activities in college, as a form of environmental education implementation.